Motivation Sukadi Build Gardens Guava (Psidium guajava)at Air Kumbang BaktiVillage Of Air Kumbang Districts Banyuasin Regency - Trimursito, Sigit; H. Anang, Rahidin; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
This study aimed to determine the profile of farmers Sukadi as guava and to find the motivation Sukadi build guava orchard at Air Kumbang BaktiVillage Of Air Kumbang Districts Banyuasin Regency. This research was conducted at Air Kumbang BaktiVillage Of Air Kumbang Districts Banyuasin Regency in March to May 2015. The method used is the case study method (case study). While the sampling method used is a method of intentionally (purposive sampling) and the method by coincidence (incidental sampling) with samples Sukadi as guava farmers, communities, farmers and agricultural extension guava at Air Kumbang Bakti Village. Data collection technique used observation and interview methods. Analysis of the data used is descriptive qualitative analysis. The survey results revealed that the profile of farmers guava Sukadi as a figure of farmers who have a hard working attitude, diligent and tenacious in to farm. Furthermore, the results showed that Sukadi motivated to build a guava orchard as seen from a technical standpoint (how cultivation) guava can already be done and in terms of economic (profit) that guava is profitable and able to meet the economic needs of the family. Moreover, in terms of the social that Sukadi want to raise the name of the Air Kumbang Bakti Village with guava orchard that he try.